Factors Determining the Success of Therapeutic Lifestyle Interventions in Diabetes – Role of Partner and Family Support. Issue 1 (2019) - Gupta, Yasheep; Lal, Priti Rishi; Khandelwal, Deepak; Gupta, Lovely; Dutta, Deep; Kalra, Sanjay
No abstract available